2017
DOI: 10.1111/pce.13085
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression trade‐offs between defence and growth inEnglish elm induced byOphiostoma novo‐ulmi

Abstract: Wilt diseases caused by vascular pathogens include some of the most damaging stresses affecting trees. Dutch elm disease (DED), caused by the fungus Ophiostoma novo-ulmi, destroyed most of North American and European elm populations in the 20th century. The highly susceptible English elm, also known as Atinian clone, suffered the highest mortality rates during the last pandemic event, probably due to its lack of genetic diversity. To study the DED pathosystem, we inoculated English elm ramets with O. novo-ulmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 72 publications
4
17
0
Order By: Relevance
“…AtFLA1/2/8 were decreased by pathogen challenge, oxidative stress and in ascorbate-deficient vtc mutants [44]. The fungus Ophiostoma novo-ulmi reduced the expression of FLAs in English elm ramets [45]. Our results…”
Section: Discussionsupporting
confidence: 58%
“…AtFLA1/2/8 were decreased by pathogen challenge, oxidative stress and in ascorbate-deficient vtc mutants [44]. The fungus Ophiostoma novo-ulmi reduced the expression of FLAs in English elm ramets [45]. Our results…”
Section: Discussionsupporting
confidence: 58%
“…AtFLA1/2/8 were decreased by pathogen challenge, oxidative stress and in ascorbate-de cient vtc mutants [49]. The fungus Ophiostoma novo-ulmi reduced the expression of FLAs in English elm ramets [50]. Our results show that almost all NbFLAs were speci cally downregulated by TuMV and Pst DC3000 infection and this suggests that NbFLAs may have speci c roles in pathogen infection.…”
Section: Discussionmentioning
confidence: 62%
“…Unlike Perdiguero et al (2018), these authors reported several JA-related genes overexpressed with the presence of O. novo-ulmi. However, the changes occurred at the inoculation point, indicating that local defense responses may be regulating differently from the responses in distal parts observed by Perdiguero et al (2018). Brand new methodologies such as RNAseq could be accurate and promising tools to achieve the goal of fully understanding the molecular aspects of elm-Ophiostoma interactions.…”
Section: Molecular Advances To Understand the Genetic Clues Behind Elmentioning
confidence: 97%
“…Recent works have advanced in this direction: U. americana trees were inoculated with O. novo-ulmi and the expression of various defense-related genes was analyzed by RT-qPCR at different hours post-inoculation in samples collected near the inoculation point (Sherif et al 2016(Sherif et al , 2017. Unlike Perdiguero et al (2018), these authors reported several JA-related genes overexpressed with the presence of O. novo-ulmi. However, the changes occurred at the inoculation point, indicating that local defense responses may be regulating differently from the responses in distal parts observed by Perdiguero et al (2018).…”
Section: Molecular Advances To Understand the Genetic Clues Behind Elmentioning
confidence: 99%
See 1 more Smart Citation